2021
DOI: 10.22541/au.161841491.18932381/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Repurposing of FDA-approved Drugs against Active Site and Potential Allosteric Drug Binding Sites of COVID-19 Main Protease

Abstract: The novel coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) still has serious negative effects on health, social life, and economics. Recently, vaccines from various companies have been urgently approved to control SARS-CoV-2 infections. However, any specific antiviral drug has not been confirmed so far for regular treatment. An important target is the main protease (Mpro), which plays a major role in replication of the virus. In this study, Gaussian and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Similarly, p‐gp is another factor associated with drug distribution across the cell membrane/efflux‐membrane transporter, directly linked to optimal drug delivery 51,52 . Overall, the computational prediction has reduced the resource and cost of selecting ideal lead candidates by filtering the essential drug parameters 52–55 . Concludingly, this cost‐effective, resource‐saving, and highly efficient computational screening is helpful to locate several repurposing candidates like marine alkaloids toward control of gruesome SARS‐CoV in this health emergency.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, p‐gp is another factor associated with drug distribution across the cell membrane/efflux‐membrane transporter, directly linked to optimal drug delivery 51,52 . Overall, the computational prediction has reduced the resource and cost of selecting ideal lead candidates by filtering the essential drug parameters 52–55 . Concludingly, this cost‐effective, resource‐saving, and highly efficient computational screening is helpful to locate several repurposing candidates like marine alkaloids toward control of gruesome SARS‐CoV in this health emergency.…”
Section: Discussionmentioning
confidence: 99%
“…From the above discussion, it can be suggested that this new quantity can be employed to identify and select an optimum set of flexible residues in the binding site for induced-fit docking (IFD) and flexible docking methods. 43,46,65,66 Based on this quantity and the values reported in Figure 2, despite the relative importance of some residues in the binding site like Cys145 and Gly143 which have contacts with the ligands in most of the complexes, around 84% and 73%, respectively, are highly rigid residues and should be removed from a set of flexible residues during IFD simulations, which is significant for achieving optimal performance of IFD protocols and saving the computation time. Moreover, it is clear from the values of residue flexibility in Figure 2 that the segment Gly143-Cys145 which defines the "oxyanion hole" as an essential part of the substrate-binding pocket represents considerable structural rigidity, in agreement with computational observations.…”
Section: Pocket-ligand Detectionmentioning
confidence: 94%
“…Finally, as an interesting case, Ser144 which interacts with its ligands in ~58.2% of the complexes is the most rigid residue for which there are only two RMSD matrix elements with values of more than 1.0 Å (0.01% of the RMSD matrix elements), and therefore, this residue has a similar configuration in almost all studied complexes. From the above discussion, it can be suggested that this new quantity can be employed to identify and select an optimum set of flexible residues in the binding site for induced‐fit docking (IFD) and flexible docking methods 43,46,65,66 . Based on this quantity and the values reported in Figure 2, despite the relative importance of some residues in the binding site like Cys145 and Gly143 which have contacts with the ligands in most of the complexes, around 84% and 73%, respectively, are highly rigid residues and should be removed from a set of flexible residues during IFD simulations, which is significant for achieving optimal performance of IFD protocols and saving the computation time.…”
Section: Structural Analysesmentioning
confidence: 99%
“…Recent studies on computer‐aided drug screening showed that bromocriptine probably inhibits the SARS‐CoV‐2 replication by exhibiting high binding affinity for both viral RNA‐dependent RNA polymerase and SARS‐CoV‐2 3C‐like protease enzymes 369,370 . Because bromocriptine is widely used clinically as well for a variety of other diseases with high safety profile and cost‐effectiveness, they repurposed it either alone or as an adjuvant with other currently used therapies in the treatment of COVID‐19 371–374 . Moreover, low dose bromocriptine administration has been seen to be fruitful in COVID‐19 patients presenting with NMS and various other central nervous system and endocrine system symptoms 372,375 …”
Section: Pharmacological Significance Of Bromocriptinementioning
confidence: 99%
“…369,370 Because bromocriptine is widely used clinically as well for a variety of other diseases with high safety profile and cost-effectiveness, they repurposed it either alone or as an adjuvant with other currently used therapies in the treatment of COVID-19. [371][372][373][374] Moreover, low dose bromocriptine administration has been seen to be fruitful in COVID-19 patients presenting with NMS and various other central nervous system and endocrine system symptoms. 372,375…”
Section: Bromocriptine In Viral Infectionsmentioning
confidence: 99%